Novel mutation in efflux pump Rv1258c (Tap) gene in drug resistant clinical isolates of Mycobacterium tuberculosis in Iran - ShimaSadat Farzaneh; Fatemeh Norouzi; Hossein Fazeli; Mahshid Salehi; Marzieh Safari; Bahram Nasr Esfahani (Journal of Infection in Developing Countries)
Introduction: Tuberculosis (TB) remains a serious public health problem worldwide. Drug-resistant TB is considered a major and growing global threat. Despite the great variety of described mutations in Mycobacterium tuberculosis (MTB) resistance genes, the mechanisms of drug resistance are still controversial. Recently, a report on the role of efflux pump genes in drug resistance added to this complexity. Therefore, a thorough understanding of efflux pump genes in drug-resistant TB clinical isolates is needed.